Health advisor facilitated mouth care regime for patients with head and neck cancers undergoing intensity-modulated radiotherapy. Issue 4 (30th July 2015) - Stringer, J.; Knowles, R.; Finchett, C.; Mackereth, P.; Mannan, J.; Slevin, N.
Abstract: Aim: To develop a regime of care for patients with head and neck cancers undergoing intensity-modulated radiotherapy (IMRT), with the support of a health advisor (HA) and temporary access to the mouth care product Caphosol™. Materials and methods: A HA was temporarily employed to assess, monitor and refer patients as appropriate and ensure patients received and utilised supplies of Caphosol™. A retrospective audit was undertaken to provide a gap analysis of current service. The data were used to develop a pro forma for documenting assessments and monitoring lifestyle factors for IMRT patients. Assessments referrals and compliance, plus hospital admissions owing to treatment-related issues, were documented during the baseline audit and the temporary HA service and provision of Caphosol™. Results: The presence of a HA facilitated 100% compliance with appropriate assessments, referrals and adherence to treatment. The data suggests that the additional provision of Caphosol™ may have reduced levels of mucositis and associated pain. Conclusion: It is recommended that a HA role be established within radiotherapy departments to facilitate lifestyle assessments, referrals and compliance with positive behaviour changes (e.g., stopping smoking). The use of Caphosol™ as a routine part of mouth care regime for IMRT patients also warrants further investigation.